2013
DOI: 10.1210/jc.2012-3930
|View full text |Cite
|
Sign up to set email alerts
|

Allele Percentage of theBRAFV600E Mutation in Papillary Thyroid Carcinomas and Corresponding Lymph Node Metastases: No Evidence for a Role in Tumor Progression

Abstract: Context:The relevance of the BRAF V600E mutation in papillary thyroid carcinoma (PTC) as a negative prognostic factor is a subject of intense debate. This mutation has been associated with several clinicopathological features, but the lack of consistency among data does not support its usefulness as marker of tumor aggressiveness and poorer outcome. Due to the genetic heterogeneity of the tumor, both the occurrence and the allele percentage of the BRAF mutation should be considered to unravel this controversy.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
63
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(73 citation statements)
references
References 46 publications
9
63
1
Order By: Relevance
“…BRAF V600E mutation was present in 54 of the 121 PTC samples analyzed (frequency: 0.44). As previously described, no association between the occurrence of this mutation and the presence of distant metastases was detected (31,32). An association between the presence of TERT C228T and BRAF V600E was observed in the DM-PTCs group (46% of TERT C228T-mutated in BRAFpositive cases vs 14% in BRAF-negative cases; PZ0.03).…”
Section: Association Of Tert Promoter Mutations Braf V600e Mutationsupporting
confidence: 53%
See 1 more Smart Citation
“…BRAF V600E mutation was present in 54 of the 121 PTC samples analyzed (frequency: 0.44). As previously described, no association between the occurrence of this mutation and the presence of distant metastases was detected (31,32). An association between the presence of TERT C228T and BRAF V600E was observed in the DM-PTCs group (46% of TERT C228T-mutated in BRAFpositive cases vs 14% in BRAF-negative cases; PZ0.03).…”
Section: Association Of Tert Promoter Mutations Braf V600e Mutationsupporting
confidence: 53%
“…Part of these samples corresponded to the cases described in previous studies (31,32). All the patients underwent total thyroidectomy and in 80% of the cases they underwent also ipsilateral central neck dissection.…”
Section: Patient Selectionmentioning
confidence: 99%
“…However, the subclonality of the BRAF mutation in PTCs has recently been suggested (Guerra et al 2012a). In this context, the quantification of the mutated allele was emphasised in terms of predicting prognosis (Guerra et al 2012b); however, several studies have shown results contradictory to those findings, as determined by the quantification of mutated alleles (Gandolfi et al 2013) and immunohistochemical (IHC) staining (Ghossein et al 2013). The proper value of the quantification of the mutated allele remains in debate and requires further evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…This represents a crucial issue with possible dramatic impact not only on the biological perspective but also on clinical implications related to the mutation, with the inclusion of the prognostic role. Particularly, 2 studies (Guerra et al 2012b, Gandolfi et al 2013) opened a burning issue among researchers dealing with thyroid carcinogenesis. In both papers, authors searched for BRAF V600E in PTC samples by means of pyrosequencing, a sequencing-by-synthesis method providing the exact percentage of alleles (and therefore cells) bearing the mutation (Ronaghi et al 1998).…”
Section: Braf V600ementioning
confidence: 99%